The Role Of Folklore In The Upbringing Of Patriotism Of Primary School Children With Hearing Impairments - Akhmediyeva, Kulmariya; Autayeva, Akbota
This article examines the problem of fostering patriotism in younger schoolchildren with hearing impairments and the importance of the pedagogical potential of folklore in this process. The study aimed to substantiate the pedagogical potential of folklore in the upbringing of patriotism in younger schoolchildren with hearing impairments. Research methods include the study and analysis of psychological, pedagogical, methodological, and special literature, as well as conducting experimental work with the introduction of empirical research methods. The experimental part of the study was conducted on teachers and teachers of a special school, and the results were achieved. Throughout the study, we identified the pedagogical potential of folklore and its use by teachers in the upbringing of patriotism of younger students with hearing impairments.
Keywords: Pedagogy